Video game addiction and sociability in high school students in the San Martín region - Araujo Morales, Luz Victoria (2022)
Objective: To determine if there is a significant relationship between addiction to video games andsociability in fifth grade students from schools in the San Martín region. Methodology: Non-experimentaldescriptive correlational design, with a sample of 308 students of both sexes between the ages of 15and 17, to whom the Video Game Scale (GAS) and the Social Skills Assessment List were applied.Results: The results showed that there is a significant and inverse relationship between video gameaddiction and sociability (rho=-0.756; p=0.000), at the same time the relationship between video gameaddiction and sociability dimensions was evidenced, that is, there is a significant, considerable andinverse relationship with assertiveness (rho=-0.679; p= 0.000), communication (rho=-0.677; p= 0.000),self-esteem (rho=-0. 696; p= 0.000) and decision making (rho=-0.645; p= 0.000). Conclusion: Thegreater the addiction to video games, the lower the sociability, generating difficulties in assertiveness,communication, self-esteem and decision-making.